PENGARUH PENGGUNAAN CANVA TERHADAP BELAJAR MENULIS TEKS PROSEDUR - Nugroho, Wahyu (Jurnal Citra Pendidikan, 2023)
This study aims to identify the effect of Canva on learning to write student procedure texts at SMK Negeri 2 Trenggalek. This research design is in quantitative research and is conducted with quasi-experimental research. This research uses two types of variables. The first variable is Canva, which will affect the dependent variable. Which was goinh to get effect from dependent variable. The sample of this study is X grade students of SMK Negeri 2 Trenggalek. Researchers chose X RPL B as the control group and X AK B as the experimental group. Each class has thirty-six students, but the total number of students participating in this study is eighteen members in each class. The instruments used in this study were tests, there were pre tests and post tests. The researcher gave a pre test to both classes before conduchting the treatment. Then, the post test was given to both classes after the researcher applied the treatment in the experimental class. The test consists of questions that students must rewrite procedural text through Canva media. After the data is collected, the researcher will analyze the data using an independent sample T-Test. Before conducting an independent sample t-test, researchers must conduct a normality test: Based on the results of the data, the Sig. value in Saphiro-Wilk of experimental group 0.188 is greater than 0.05 and Sig. in Saphiro-Wilk of Control Group 0.036 is greater than 0.05. This means that the samples in this study are normally distributed. Based on the "Independent Sample Test", Sig. (2-tailed) of the posttest is 0.026 <0.05. then as a basic rule for making an independent sample t-test it can be concluded that Ho is rejected and Ha is accepted. Thus, it can be concluded that there is a significant effect of students' procedure text writing learning in the experimental group and control group. Based on this result. Canva as the treatment of this research is an effective learning media for learning to write procedure texts for students. The results of this study indicate that the use of Canva in learning English at SMK is the right choice for teachers, and Canva application is very useful in the teaching and learning process. In addition, this media helps students in learning, because it can be accessed anytime, and anywhere. So, Canva is a media that can be used to increase the level of motivation and learning ability of students. It is one of the effective media in learning writing for students in high school.